Preparation and evaluation of a nosocomial delivery system containing g. mangostana extract and study of its anti-acanthamoeba activity - Suthinee Sangkana; Komgrit Eawsakul; Tassanee Ongtanasup; Rachasak Boonhok; Watcharapong Mitsuwan; Siriphorn Chimplee; Alok K. Paul; Shanmuga Sundar Saravanabhavan; Tooba Mahboob; Muhammad Nawaz; Maria L. Pereira; Polrat Wilairatana; et al. (Nanoscale Advances, 2024)
Garcinia mangostana extract (GME) has severe pharmacokinetic deficiencies and is made up of a variety of bioactive components. GME has proven its anti-Acanthamoeba effectiveness. In this investigation, a GMEloaded niosome was developed to increase its potential therapeutic efficacy. A GME-loaded niosome was prepared by encapsulation in a mixture of span60, cholesterol, and chloroform by the thin film hydration method. The vesicle size, zeta potential, percentage of entrapment efficiency, and stability of GME-loaded niosomes were investigated. The values for GME-loaded niosome size and zeta potential were 404.23 ± 4.59 and −32.03 ± 0.95, respectively. The delivery system enhanced the anti-Acanthamoeba activity, which possessed MIC values of 0.25–4 mg mL−1 . In addition, the niosomal formulation decreased the toxicity of GME by 16 times. GME-loaded niosome must be stored at 4 °C, as the quantity of remaining GME encapsulated is greater at this temperature than at room temperature. SEM revealed the damage to the cell membrane caused by trophozoites and cysts, which led to dead cells. In light of the above, it was found that GME-loaded niosomes had better anti-Acanthamoeba activity. The study suggested that GMEloaded niosomes could be used as an alternative to Acanthamoeba's therapeutic effects.